2005
DOI: 10.1590/s0037-86822005000600017
|View full text |Cite
|
Sign up to set email alerts
|

Inquérito epidemiológico sobre teníase em população do programa saúde da família no município de Uberaba, MG

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
0
5
0
5
Order By: Relevance
“…Cross-sectional population-based studies have been widely used to determine prevalence and for diagnosis in health for both national [35][36][37][38][39] and international levels [40][41][42] . In the case of the surveys that address the issue of disability, the incorporation of the concepts advocated by the WHO, through the ICF, is crucial for the estimation of the prevalence of disabilities not to be impaired, and that the results are not biased.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional population-based studies have been widely used to determine prevalence and for diagnosis in health for both national [35][36][37][38][39] and international levels [40][41][42] . In the case of the surveys that address the issue of disability, the incorporation of the concepts advocated by the WHO, through the ICF, is crucial for the estimation of the prevalence of disabilities not to be impaired, and that the results are not biased.…”
Section: Discussionmentioning
confidence: 99%
“…In Uberaba County, Minas Gerais, Brazil, Esteves et al (2005) observed that only 185 (0.2%) individuals out of 100,144 from both rural and urban areas assisted by the Family Health Program had a history of taeniasis. Among the latter, 112 (60.5%) had been treated with anthelmintic agents, allowing for the recovery of proglottids or adult taenia from the feces of 97 patients (86.6%), of which 36 (37.1%) were Taenia saginata and four (4.1%) were T. solium.…”
Section: Discussionmentioning
confidence: 99%
“…Considerando a maior prevalência de teníase por T. saginata (Dias et al 1991, Esteves et al 2005, bem como a similaridade morfológica entre T. saginata e T. asiatica (Eom & Rim, 1993, Fan et al 1995, que é considerada exótica no país, aliadas à endemicidade de cisticercose humana em muitos estados brasileiros (Machado et al 1988, Agapejev 1996, Takayanagui & Leite 2001, Mendes et al 2005 e às baixas taxas de ocorrência da cisticercose suína (Alves 2000, Flavigna-Guilherme et al 2006), ao contrário do que se observa em bovinos, torna-se imperiosa a necessidade de aprofundar as análises moleculares, com vistas ao esclarecimento de muitos pontos controversos que permanecem no universo cientíϐico, a começar com a possibilidade dos ovos de T. saginata causarem cisticercose no homem, conforme admitiram Santos (1996) e outros autores citados por Pardi et al (2001). Quanto à identiϐicação de C. bovis nos diversos sítios anatômicos estudados, mais uma vez destaca-se a importância de se tornar rotina nos matadouros, os exames de esôfago e ϐígado, pois os resultados encontrados na PCR conϐirmaram o diagnóstico ambulatorial feito nessas localizações.…”
Section: Resultsunclassified